Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10856-013-4924-3
|View full text |Cite
|
Sign up to set email alerts
|

The concentrations of IL-8 and IL-6 in gingival crevicular fluid during nickel–chromium alloy porcelain crown restoration

Abstract: We explored gum irritation and cytotoxicity caused by nickel-chromium (Ni-Cr) alloy porcelain by interleukin-8 (IL-8), interleukin-6 (IL-6) and gingival crevicular fluid (GCF) volumes at different time points peri-crown restoration. This prospective study was conducted in 60 young adults. The total amount and concentrations of IL-8 and IL-6 per site, GCF volumes, and blood neutrophil counts were performed prior to and at 1 week, 3 months, and 6 months after Ni-Cr alloy-porcelain crown restoration. Thirty male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A variety of inflammatory mediators such as IL-1α, TNF-α, IL-1β, IL-6, MIP-1, IL-8, IL-1ra, CRP, PGE2 and IgG have been used to gain insight into the inflammatory response as a consequence of the use of different prosthetic restorative materials [27][28][29][30][31][32][33][34][36][37][38][39][40][41] and even some enzymes such as resistin, aspartate aminotransferase, alkaline phosphatase and matrix metalloproteases (MMPs), mainly MMP-2, MMP-8, aMMP-8 and MMP-9, which have been implicated in the destruction of periodontal tissues [26,35] (Table 1). [41] GCF: gingival crevicular fluid; Ni-Cr: nickel-chromium; Cr-Co: chromium-cobalt; Au-Pt: gold-platinum; Cr-Ni-M: chromium-nickel-molybdenum; TNF-α: tumor necrosis factor alpha; CRP: C-reactive protein; YKL-40: chitinase 3like protein 1; AST: aspartate aminotransferase; ALP: alkaline phosphatase; IL-6: interleukin 6; IL-8: interleukin 8; IL-1 α: interleukin 1 alpha; IL-1β: interleukin 1 beta; IL-1ra: interleukin 1 receptor antagonist; MIP-1α: macrophage inflammatory protein 1 alpha; MIP-1β: macrophage inflammatory protein 1 beta; PGE2: prostaglandin E2; MMP-2: matrix metalloprotease 2; MMP-8: matrix metalloprotease 8; aMMP-8: matrix metalloprotease 8 in its active form; MMP-9: matrix metalloprotease 9; TIMP-1: tissue inhibitor of metalloproteases 1; TIMP-2: tissue inhibitor of metalloproteases 2; IgG: immunoglobulin G.…”
Section: Biomarkers Of Inflammation In Relationship To the Use Of Fix...mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of inflammatory mediators such as IL-1α, TNF-α, IL-1β, IL-6, MIP-1, IL-8, IL-1ra, CRP, PGE2 and IgG have been used to gain insight into the inflammatory response as a consequence of the use of different prosthetic restorative materials [27][28][29][30][31][32][33][34][36][37][38][39][40][41] and even some enzymes such as resistin, aspartate aminotransferase, alkaline phosphatase and matrix metalloproteases (MMPs), mainly MMP-2, MMP-8, aMMP-8 and MMP-9, which have been implicated in the destruction of periodontal tissues [26,35] (Table 1). [41] GCF: gingival crevicular fluid; Ni-Cr: nickel-chromium; Cr-Co: chromium-cobalt; Au-Pt: gold-platinum; Cr-Ni-M: chromium-nickel-molybdenum; TNF-α: tumor necrosis factor alpha; CRP: C-reactive protein; YKL-40: chitinase 3like protein 1; AST: aspartate aminotransferase; ALP: alkaline phosphatase; IL-6: interleukin 6; IL-8: interleukin 8; IL-1 α: interleukin 1 alpha; IL-1β: interleukin 1 beta; IL-1ra: interleukin 1 receptor antagonist; MIP-1α: macrophage inflammatory protein 1 alpha; MIP-1β: macrophage inflammatory protein 1 beta; PGE2: prostaglandin E2; MMP-2: matrix metalloprotease 2; MMP-8: matrix metalloprotease 8; aMMP-8: matrix metalloprotease 8 in its active form; MMP-9: matrix metalloprotease 9; TIMP-1: tissue inhibitor of metalloproteases 1; TIMP-2: tissue inhibitor of metalloproteases 2; IgG: immunoglobulin G.…”
Section: Biomarkers Of Inflammation In Relationship To the Use Of Fix...mentioning
confidence: 99%
“…Several prosthetic materials are used for the fabrication of fixed dental prostheses (as shown in Figure 1 ), including metal-ceramic and metal-free ceramics such as zirconium oxide and lithium disilicate [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], as well as polymeric materials such as polymethylmethacrylate (PMMA), with the latter mainly used for provisional purposes [ 28 , 42 ].…”
Section: Biomaterials Used In Fixed Dental Prosthesismentioning
confidence: 99%
“…In a prospective study involving 60 young adults, the biocompatibility of Ni−Cr cast alloy was characterized using the pro-inflammatory markers, interleukin-8 (IL-8), interleukin-6 (IL-6), as well as gingival crevicular fluid (GCF) volume. 119 It was shown that the increase in IL-8, IL-6 and GCF volume could be attributed to the cytotoxicity of Ni−Cr alloys. Cobalt−chromium (Co−Cr) alloys have also been shown to be cytotoxic to human gingival fibroblasts (HGF).…”
Section: Wettabilitymentioning
confidence: 99%
“…Some of the widely measured responses include cytotoxicity, proliferation, integration of bone and soft tissue, inflammatory responses, and cell differentiation potential . Some alloys are toxic to cells over time, due to the leaching of ions, as discussed above. To examine biocompatibility, various metallic alloy of nickel, chromium, titanium, and zirconium have been studied. In a prospective study involving 60 young adults, the biocompatibility of Ni–Cr cast alloy was characterized using the pro-inflammatory markers, interleukin-8 (IL-8), interleukin-6 (IL-6), as well as gingival crevicular fluid (GCF) volume .…”
Section: Implant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation